PENERAPAN NILAI-NILAI PENDIDIKAN ISLAM OLEH PENYELENGGARA PEMILU DI SULAWESI BARAT - Rustang, Rustang; Abbas, Abbas; Muslimin, Abdul Azis (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This research examines the application of Islamic education values by election organizers in West Sulawesi, with a focus on integrity, transparency, justice, and responsibility in the process of organizing elections. These values are an important foundation in maintaining the quality and legitimacy of democracy in Indonesia. This research is a descriptive qualitative study, identifying a range of relevant Islamic education values, such as faith, honesty and cooperation, that are applied by election organizers in their daily tasks. The study involved interviews with the Chairperson, Members, and Secretariat of the KPU and Bawaslu of West Sulawesi Province, as well as analysis of relevant documents. The results show that the implementation of Islamic education values by election organizers not only strengthens the integrity of the electoral process, but also increases public trust in the election results. Nevertheless, there are challenges in internalizing and applying these values, especially in the face of political pressure and regulations that are not yet fully supportive. This research suggests the need for collaboration between the government, educational institutions and the community to ensure that Islamic education values are not only formally applied, but also internalized by all parties involved in organizing elections. Thus, it is hoped that the electoral process in Sulawesi can run better, fairer, and more reliable, in accordance with noble Islamic principles.